TINGKAT KESEJAHTERAAN PETANI TAMBAK UDANG DI DESA KALISOGO KECAMATAN JABON KABUPATEN SIDOARJO - Tyamaudy Subyantoro; Ida Nuraini; Hendra Kusuma (Program Studi Ekonomi Pembangunan, 2020)
The purpose of this study was to determine the level of welfare of shrimp farm farmers in Kalisogo Village, Jabon District, Sidoarjo Regency and determine the effect of price variables, production variables, and land area variabels on Farmer exchange rates. This type of research is quantitative research. The population in this study was 187 shrimp farm farmers in Kalisogo Village, Jabon District, Sidoarjo Regency and the sample of this study was 38 respondents in shrimp pond farmers in Kalisogo Village, Jabon District, Sidoarjo Regency.The technical analysis used is multiple linear regression and the farmer exchange rate method. The results of this study indicate that the production variable has a positive effect on the farmer exchange rate variable and the land area variable has a positive effect on the farmer exchange rate variable while the price variable has no significant effect on the farmer exchange rate variable. the farmer exchange rate method if more than 100 then experiences a surplus of the overall yield of 102,84 which means that the farmer exchange rate is fulfilled and can be further developed.